Legal Protection for Minors as Perpetrators of Sexual Violence (Journal of Creativity Student, 2021)
This study aims to find out how the legal protection for children as perpetrators of violent crimes against children is, then how are the obstacles to legal protection for children as perpetrators of violent crimes against fellow children. The method used in this study is a juridical, empirical method, and uses a descriptive qualitative approach. The data collected is based on an analysis of events that actually happened. The data is obtained from trusted journals, books and articles. The results of the study indicate that legal protection for children as perpetrators of criminal acts of violence against fellow children is essentially an effort made by parents, government and society to fulfill and guarantee all children's rights that have been guaranteed in the Convention on the Rights of the Child and Law Number 35 2014 concerning Child Protection. Legal protection for children as perpetrators of violence against fellow children is not implemented because the government has not carried out its obligations in fulfilling children's rights so that there are still violations of the law against children. In implementing legal protection for children as perpetrators of violent crimes against fellow children, parents should be fully responsible for the behavior of children and the government should set policies that are in line with the wishes of the community, so that there is a common perception between parents, government and society in fulfilling children's rights.